CORAL SNAKE ANTIVENOM PRODUCED IN CHICKENS (Gallus domesticus) - Irma Aguilar (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The production of anti-snake venom from large mammal's blood has been found to be low-yielding and arduous, consequently, antivenom immunoglobulins for treatment are achieved regularly as polyvalent serum. We have standardized an undemanding technique for making purified immunoglobulin IgY antivenom consisting of polyclonal antibodies against coral snake venom in the egg yolk of immunized hens. We have adapted a reported process of antibody purification from egg yolks, and achieved 90% antibody purity. The customized technique consisted of the removal of lipids from distilled water-diluted egg yolks by a freeze–thaw sequence. The specific immunoglobulins were present in the egg yolk for up to 180 days postimmunization. Therefore, by means of small venom quantities, a significant amount of immunoglobulins were found in an adequately purified state (The obtained material contained about 90% pure IgY). The antigen binding of the immunoglobulins was detected by a double immunodiffusion test. Titers of antibodies in the yolk were estimated with a serum protection assay (Median effective dose = ED50) (ED50= 477 mg/kg). Given that breeding hens is economically feasible, egg gathering is noninvasive and the purification of IgY antibodies is quick and easy, chicken immunization is an excellent alternative for the production of polyclonal antibodies. To the best of our knowledge, this is the first coral snake antivenom prepared in birds.